Організація сучасних систем периметральної охорони - Сливар, У. М. (ХНУРЕ, 2023)
The thesis is devoted to the study of perimeter protection systems that provide security for objects of various purposes, as well as demonstration of its effectiveness. Methods and means of external security of the object.
Keywords: периметральна охорона